Våldtäkt som krigsvapen – En studie om våldtäktsbrottets definition och dess reglering i väpnade konflikter sedan 1900-talet, med särskilt fokus på rättsfallen Akayesu, Furundžija och Kunarac - Karlsson,Melina (2024)
This thesis has clarified the development of the definition of rape and the legal protection against rape in armed conflicts since the 1900s. A legal dogmatic method has been used with an emphasis on the sources of law in international law, where two central research questions have been reviewed. This study has examined current law, including three groundbreaking legal cases: Akayesu, Furundžija and Kunarac. The perception of sexual violence, especially rape, has undergone a significant transformation. Since the 1900s, rape has gone from being considered as a crime against the family´s honor, to being recognized as a serious breach of international law that can cause severe physical and psychological damages to victims. Although the Geneva Conventions from 1949 and their Additional Protocols from 1977 statute that women shall be protected from sexual violence, rape is not defined as a war crime. After reports of the widespread rapes in Rwanda 1994, the UN Security Council established an ad hoc tribunal to bring the perpetrators to justice. In this study, the legal case Akayesu from 1998 issued by the Tribunal has been analyzed. This was the first case at an international court where sexual violence was classified as both genocide and a crime against humanity. The outcome was that all states gained jurisdiction to prosecute rapes in armed conflicts. In the legal case, a broad definition of rape was established that included acts that previously fell outside the boundaries of the definition of rape. During the conflict in the former Yugoslavia (1992–1995), systematic rapes were committed. Also here, the UN Security Council created an ad hoc tribunal to bring the perpetrators to justice. In this study the legal case Furundžija from 1998 issued by the Tribunal has been reviewed. This was the first case for war crimes where rape and sexual violence were the only accusations and which was based on charges of rapes against a single victim. In the case, the definition of rape was extended to explicitly include oral penetrations. Also the legal case Kunarac which was decided by the Tribunal in 2001 has been studied. This was the first case from this Tribunal to condemn rape as a crime against humanity. Here, for the first time, sexual autonomy was emphasized as a central factor in determining if rapes had been committed. Together, these cases have contributed to create a more inclusive and extensive definition of rape under international law. Shortly before the Akayesu case, the Rome Statute was introduced in 1998, establishing that rapes in armed conflicts can constitute a crime against humanity, a war crime and, indirectly, a crime of genocide. The Statute allows for prosecution of violations at the International Criminal Court. Between 2000 and 2019, the UN Security Council adopted several resolutions which strengthens the protection for vulnerable women and confirms that sexual violence can constitute both a crime against humanity and genocide. These resolutions also encourage national authorities to promote accountability for sexual violence. Furthermore, the ICRC, through its study from 2005 about international custom, confirmed that rape is prohibited in armed conflicts. The analyzed legal cases have played a decisive role in advancing the regulation of international law in this area.
Keywords: Folkrätt; public international law; våldtäkt; rape; sexuellt våld; sexual violence; ICTY; ICTR; Akayesu; Furundžija; Kunarac